Stable isotopes as indicators of ecological change (Elsevier, 2007)
Content of book provides researchers with groundbreaking data on how to predict the terrestrial ecosystems response to the ongoing rapid terations Reveals how ecosystems have responded to environmental and biotic in the past; Includes examples from research by a wide range of biological and physical scientists who are using isotopic records to both detect and interpret environmental change.